Indeks Massa Tubuh (IMT) dengan Kadar Hemoglobin Remaja Putri - Febriayanti S, Rika; Masfufah Masfufah; Ni Ketut Kariani (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Anemia is a condition experienced by the body when red blood cells have hemoglobin levels less than the normal limit (<12 gr/dl). Adolescent groups, especially young women, are susceptible to anemia because they menstruate every month. One of the factors causing anemia in adolescent girls is poor nutritional status. Wrong eating habits, such as being lazy about eating and liking to eat fast food instead of home-cooked food, cause insufficient nutrition, thus affecting the nutritional status of young women. The aim of this research is to determine the relationship between Body Mass Index (BMI) and hemoglobin levels in adolescent girls.  This type of quantitative research uses a cross sectional method. The population is 406 young women from the Mamboro Community Health Center Area High School. The sample was 89 female students with a sampling technique, namely cluster random sampling. Data analysis uses the Chi Square test. The results of the study showed that the majority of young women with BMI were thin at 56.2% and there was a relationship between BMI and hemoglobin levels of young women with a P-Value of 0.000 <0.1. The conclusion of the study is that there is a relationship between BMI and hemoglobin levels in adolescent girls.